The Usefulness of Analysts’ Target Prices to Foreign Institutional Investors: U.S. Evidence - Ahmed Al-Dmour; Hala Zaidan; Abdulrahman Alnatour (Australasian Accounting, Business and Finance Journal, 2020)
This paper investigates whether foreign institutional investors in the United States earn future returns by responding to analysts target price revisions. to examine this issue, this study is using firm fixed effect and industry fixed effect regression in order to examine the effect of using analyst’s target price revisions on future abnormal return for foreign institutional investors. We used 51,427 firm-quarter observations between 2003 and 2013 in the U.S. equity market. Different robust approaches were used to proxy foreign institutional trading. We find a positive and significant increase in foreign institutional ownership in response to a positive change in analysts’ target prices, which predict positive stock returns. The results are robust to controlling for other analysts’ outputs, such as revisions to their earnings’ forecasts and stock recommendations, in addition to other determinants of institutional trading. These results are also robust using different measures of institutional trading. In addition, the results show that foreign institutional trading based on target prices’ revisions is more pronounced in firms with high information asymmetry. The results show that foreign institutional investors rely more on analysts in small firms and firms with low analyst coverage.
Keywords: Sell-Side analysts; institutional trading; institutional foreign investors; information asymmetry; target price revisions